Carfilzomib is an effective upfront treatment in AL amyloidosis patients with peripheral and autonomic neuropathy. (6th August 2019) - Manwani, Richa; Mahmood, Shameem; Sachchithanantham, Sajitha; Lachmann, Helen J.; Gillmore, Julian D.; Yong, Kwee; Rabin, Neil; Popat, Rakesh; Kyriakou, Charalampia; Worthington, Sarah; Sharpley, Faye; Smith, Mark; et al.
Summary: Bortezomib is standard treatment in AL amyloidosis (AL), but is contraindicated in patients with significant neuropathy. Carfilzomib, a second‐generation proteosomal inhibitor, results in a lower incidence of neuropathy than bortezomib, but data in AL is scant. We report a cohort of five AL patients treated with upfront carfilzomib. All had cardiac, peripheral and autonomic neuropathy at presentation. All achieved at least a very good partial haematological response. There was no worsening in cardiac function, peripheral or autonomic neuropathy. Carfilzomib is an effective upfront treatment option in AL patients with peripheral and/or autonomic neuropathy (without severe cardiac or renal involvement).